Berît ʻôlām w wyroczniach proroków niewoli - Szwarc, Urszula (The Biblical Annals, 2017)
The paper is an analysis of the oracle in Ezek 16, 60-61a; 37, 26; Is 55, 3; 61, 8. It allows to state that the prophets of the time of the Babylonian slavery basically took the concept „everlasting covenant” to mean a new covenant between God and Israel. As a result of this Jahve will for ever live among His people. The nation will be internally and spiritually transformed, so that they will never be unfaithful to their God.